A Perspective Plan for The Development of Primary Education in India (1966-1986) - Ministry of Education, Government of India (Ministry of Education, Government of India, 1968)
The total duration of school education, in the opinion of the Commission, should be 12 years. This has also been the recommendation of the Sadler Commission (1917-19) and the Radhakrishnan Commission (1948-49). The Education Commission also found that the best way to sub-divide this period would be to provide primary education for seven years and secondary education for five years (which should be further divided into two sub-stages - three years of lower secondary and two years of higher secondary education).
Ministry of Education, Government of India
Ministry of Education, Government of India